Baking problems solved - Cauvain, Stanley P. (CRC Press ; Woodhead Pub., 2001)
When things go wrong in the bakery, the pressures of production do not allow time for research into the solution. Solving these baking problems has always been the province of 'experts'. However, with a methodical approach, keen observation and a suitable reference book then the answers to many bakery problems are straightforward. Baking problems solved is designed to help the busy bakery professional find the information they need quickly. It also enables them to understand the causes and implement solutions. It is arranged in a practical question-and-answer format, with over 200 frequently asked questions. Individual chapters consider the essential raw materials and the main types of bakery products. This book is of invaluable use to all bakery professionals, bakery students, food technologists and product developers. Provides immediate solutions to the most frequently encountered problems in bakingEasy to use and invaluable guidance on improving production and quality in bakery productsWritten by award winning internationally renowned experts.
Keywords: Baking.; elektronické knihy; electronic books